Spectrophotometrically Determination of Fe(III) in Manganese Processing Waste Water with Ethanol Extract of Terminalia catappa L. Leaves as a Complexing Agent - Ola, Pius D.; Beti, Milce Y.; Wogo, Hermania Em; Darmakusuma, Dodi (Universitas Nusa Cendana, 2021)
Chemical analysis, including metal ions determination using the spectrophotometry method, involves using a complexing agent, mostly produced by chemical industries, reacting with the analyte to form a colored compound. The very high cost and the environmentally unfriendly are the main disadvantages of that complexing agent. The use of a complexing agent categorized as a “green” chemical is critical to overcoming those shortcomings. In this work, extract ethanol of Terminalia catappa L. leaves was employed as a complexing agent in the determination of Fe(III) from aqueous media using the spectrophotometry method. The value of correlation coefficient (r) 0.993, obtained from the calibration curve, indicated that ethanol extract of Terminalia catappa L. leaves could be applied as a complexing agent for determining Fe(III) from aqueous media using the spectrophotometry method. By comparing this complexing agent with the commonly used complexing agent of Fe(III) viz KSCN, it was found that these two complexing agents did not differ significantly in the term of precision. Unlike precision, the accuracy obtained from these two complexing agents still differs significantly. When both complexing agents were applied in the determination of Fe(III) in manganese processing waste water, we found the concentration of Fe(III) was 0.009 ppm (ethanol extract as complexing agent) and 0.0076 ppm (KSCN as complexing agent). It is recommended to purify the extract before using it as a complexing agent for Fe(III) determination.